The The Influence of Transformational Leadership, Career Development, and Work Motivation on Employee OCB at PT Tanjung Priok Cirebon - Fatmawati, Ayu; Rahayu, Nilla Agustin (LPPM of NAROTAMA UNIVERSITY, 2025)
Objective: The aim of this study is to explore how work motivation, opportunities for career growth, and transformational leadership affect the organizational citizenship behavior (OCB) of employees at PT Tanjung Priok Cirebon. Design/Methodology/Approach: This research employs a quantitative approach, engaging 100 employees as subjects. A census sampling technique is utilized, ensuring that every individual within the population is included. The results reveal a connection between work motivation, career advancement, and transformational leadership with the voluntary behaviors exhibited by employees in the workplace. Findings: This investigation primarily focuses on how these three factors impact employees' readiness to exceed their official job duties. Limitations/ Implications of the study: From a practical standpoint, the findings suggest that employees’ inclination to contribute beyond their designated roles is positively linked to transformational leadership, career advancement, and work motivation. Practical Implications: This research offers a unique analysis, adding to the current body of knowledge. Originality/ Value : This paper is original Paper Type :This work is categorized as a research study.